Akibat Hukum Perceraian dan Penyelesaian Sengketa Hak Asuh Anak - Joenathan Prasetya Simamora; Ahmad Ade Inaya; Sofiatul Awaliyah (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
Divorce is a legal event that gives rise to various legal consequences for the parties involved, including the husband, wife, and children. In addition to terminating the marital relationship, divorce also raises issues regarding the rights and obligations of the parties, particularly concerning child custody. Child custody disputes often become a complex problem as they involve the best interests of the child and the conflicting interests of both parents. This article aims to analyze the legal basis for the legal consequences of divorce and to examine the problems of child custody and its resolution within the Indonesian legal system. The method used is normative legal research with a statutory approach and a conceptual approach. The results show that the legal consequences of divorce are regulated in various laws and regulations, such as the Marriage Law and the Compilation of Islamic Law. In child custody disputes, courts generally consider the best interests of the child as the primary basis for determining custody rights. Therefore, resolving child custody disputes requires a legal approach that not only ensures legal certainty but also provides protection for children's rights